Anti-Adhesive Podocalyxin Expression Is Disrupted in Recurrent Implantation Failure - Mustafa Tas (Diagnostics)
Objectives: The downregulation of anti-adhesive regulatory proteins and upregulation of adhesive genes are critical for the receptive endometrium. This study was designed to determine whether switching between the anti-adhesive podocalyxin (PDX) and adhesive HOXA10 receptivity modulator occurs in the endometrium of women with recurrent implantation failure (RIF). Methods: Twenty-four patients with RIF who could not conceive for three or more cycles despite good-quality embryo transfer constituted the study group. Twenty-four patients with unexplained infertility (UEI) matched for age, BMI, and infertility duration were included in the control group. Twenty women scheduled to undergo intrauterine device (IUD) placement for birth control were included in the comparative group. Endometrial tissue was collected from patients with RIF and UEI during egg retrieval after ovarian stimulation using the GnRH antagonist protocol. In the fertile group, endometrial tissues were collected during IUD insertion. HOXA10 mRNA expression was analyzed by qRT-PCR and PDX protein expression was analyzed by ELISA. The relative expression of endometrial HOXA10 mRNA was calculated using the 2−ΔΔCt equation. Results: The relative expression of HOXA10 mRNA in the RIF group was significantly lower than that in the UEI group (p < 0.001). HOXA10 mRNA expression in the fertile group was significantly higher than that in the RIF group and was similar to that in the UEI group. PDX expression in the RIF group was significantly higher than that in the UEI group (p < 0.001). PDX expression in the fertile group was significantly lower than in the RIF and UEI groups. A negative correlation was detected between the anti-adhesive PDX protein and adhesive HOXA10 (r = −0.797, p < 0.001). Although there was a positive correlation between endometrial thickness recorded on the day of hCG administration and HOXA10 (r = 0.590, p < 0.01), endometrial thickness was negatively correlated with PDX (r = −0.529, p < 0.01). Conclusions: The failed physiological downregulation of the anti-adhesive PDX protein in patients with RIF prevented the upregulation of adhesive HOXA10 mRNA.